(untitled) (Academicia Globe: Inderscience Research, 2022)
Focal epilepsy is one of the most common inherited forms of seizures. Focal familial epilepsies include tens of different diagnoses and have both extremely diverse symptoms and a wide range of etiological factors, in particular genetic ones. Hence, they require systematization of diagnostic and treatment methods.